Transcatheter closure of ruptured right-coronary aortic sinus fistula to right ventricle - Khoury Asaad; Khatib Ihab; Halabi Majdi; Lorber Avraham (Wolters Kluwer Medknow Publications, 2010)
A 22-year-old man was referred for evaluation of exertional fatigue. On examination, there were no overt signs of congestive heart failure. Transthoracic and transesophageal echocardiography revealed rupture of the right coronary aortic sinus of Valsalva into the right ventricle. It was successfully closed with a 12 X 10 Amplatzer duct occluder.